2015
DOI: 10.5935/abc.20150024
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms Involved in Exercise-Induced Cardioprotection: A Systematic Review

Abstract: BackgroundAcute myocardial infarction is the leading cause of morbidity and mortality worldwide. Furthermore, research has shown that exercise, in addition to reducing cardiovascular risk factors, can also protect the heart against injury due to ischemia and reperfusion through a direct effect on the myocardium. However, the specific mechanism involved in exerciseinduced cardiac preconditioning is still under debate.ObjectiveTo perform a systematic review of the studies that have addressed the mechanisms by wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 70 publications
(133 reference statements)
0
32
0
1
Order By: Relevance
“…Despite some mechanisms being known to operate in EICP – including an increment in antioxidant capacity, changes in mitochondrial phenotype and glycolytic flux, promotion of nitric oxide signalling, promotion of ATP‐dependent potassium channel function, and an increase in endoplasmic reticulum stress proteins and myocardial cyclooxygenase 2 activity – knowledge of the mechanisms responsible for EICP is limited (Borges, 2015; Kavazis et al., 2008; Powers et al., 2014; Powers et al., 2008; Quindry et al., 2012). Moreover, most studies have focused on the effects of moderate intensity continuous training, and there are limited studies on the effects of HIIT and its cardioprotective mechanisms (Fallahi et al, 2015; Rahimi et al., 2015; Ghanimati et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Despite some mechanisms being known to operate in EICP – including an increment in antioxidant capacity, changes in mitochondrial phenotype and glycolytic flux, promotion of nitric oxide signalling, promotion of ATP‐dependent potassium channel function, and an increase in endoplasmic reticulum stress proteins and myocardial cyclooxygenase 2 activity – knowledge of the mechanisms responsible for EICP is limited (Borges, 2015; Kavazis et al., 2008; Powers et al., 2014; Powers et al., 2008; Quindry et al., 2012). Moreover, most studies have focused on the effects of moderate intensity continuous training, and there are limited studies on the effects of HIIT and its cardioprotective mechanisms (Fallahi et al, 2015; Rahimi et al., 2015; Ghanimati et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Hydrogen ions and lactate levels increase, decreasing pH below 6.5. Na + /H + exchange and Na + /K + pumps are compromised as ATP levels are challenged (Borges & Lessa, 2015).…”
Section: Exercise Preconditioning and Ischaemia-reperfusionmentioning
confidence: 99%
“…The relationship between physical activity and health status has stimulated an increasing number of researchers looking at the role of chronic exercise training on telomere biology. It has been shown that regular exercise exerts a protective effect against cellular and molecular damage, attenuating the decline in physiological functions during aging, leading to a greater quality of life and lowered mortality [4,33,34,41].…”
Section: Introductionmentioning
confidence: 99%